Internalizing CO2-Equivalent Emissions Issued From Agricultural Activities - Dragicevic, Arnaud Zlatko (Frontiers in Climate, 2021)
The purpose of the following article is to consider the market-based instruments, such as the ETS system, for the internalization of the CO2-equivalent emissions issued from the agricultural sector. We use a hypothetical market valuation of the emissions and we extend the analysis to the optional pricing with double barriers. According to our results, the purpose of attaining the levels of carbon emissions recommended by the French public authorities, with a level of reductions down by 50.00% in 2030, could be successful would the terminal range of optional prices stand between 76.35 Eur and 89.56 Eur.